Temporal and spatial variations of microplastics in roadside dust from rural and urban Victoria, Australia: Implications for diffuse pollution. (August 2020) - Su, Lei; Nan, Bingxu; Craig, Nicholas J.; Pettigrove, Vincent
Abstract: Microplastic pollution is an important issue for environmental management as their ubiquity in marine and freshwaters has been confirmed. Pollution sources are key to understanding how microplastics travel from land to open oceans. Given that information regarding microplastic transport from diffuse sources is limiting, we conducted a study on roadside dust from rural and urban Victoria, Australia, over two seasons. Any deposited fugitive dust and particulate matter may also be present in our samples. The average microplastic abundance over two seasons ranged from 20.6 to 529.3 items/kg (dry weight based), with a predominant portion of fibers and items less than 1 mm. Polyester and polypropylene were the dominant polymer types (26%) while cotton and cellulose were the most common non-plastic items (27%). Sampling sites displayed consistent microplastic abundances over time and shared similar patterns in size, shape and polymer composition. Multiple correlation and principal component analysis suggest that urbanization and rainfall are important influences to roadside microplastic accumulation. The observed microplastic hotspots were generally located within close vicinity of areas where urban intensive land use and regional population sizes are high. Microplastics accumulated on roads and road verges during periods of dry weather and were flushed away during heavy storms while the corresponding trigger value was unknown. Monitoring roadside dust can be considered as an initial and cost-effective screening of microplastic pollution in urban areas. Further efforts should be made to optimize the methodologies and we advocate prolonged sampling schemes for roadside dust monitoring. Graphical abstract: Image 1 Highlights: Microplastics in roadside dusts were firstly confirmed in rural and urban Australia. Small microfibers (<1 mm) and polyesters were dominant in all samples. Urbanized streets with high population size are prone to accumulate microplastics. Microplastics can be flushed away during heavy storm. Roadside dust monitoring are useful in microplastic diffuse sources managements. Abstract : Urbanization and weather conditions are major factors to microplastic accumulation by roadsides.